Physiological and production response of dairy goats bred in a tropical climate - Souza, Priscila Teixeira de; Flores Salles, Maria Gorete; Lima da Costa, Antnio Nelson; Vidal Carneiro, Hilton Alexandre; Souza, Leonardo Peres de [UNESP]; Rondina, Davide; Araujo, Airton Alencar de (Springer, 2014)
The aim of this work was to determine the adaptability of Saanen and A1/2Saanen x A1/2Anglo-Nubian (A1/2SA1/2AN) goats bred in tropical climates. The study included 30 goats, 15 Saanen and 15 A1/2SA1/2AN. The data was collected during the rainy and dry seasons. During the whole experimental period, the environment variables were recorded, as well as rectal temperature (RT), superficial temperature (ST), respiratory rate (RR) and heart rate (HR) and milk production (MP). The adaptability coefficient (AC) was calculated for both genotypes. The averages were evaluated by ANOVA at 5 % probability. There was a genotype and period of year effect, as well as the interaction genotype x period of year. Pearson's simple correlation analysis was then carried out between milk production and physiological and environment variables. There was a statistical difference (p < 0.05) between the seasons for RT, ST and RR. RT, RR and HR were lower for A1/2SA1/2AN than Saanen goats, regardless of the season. MP was greater in the dry season (p < 0.05) (2.52 A +/- 0.50 kg/day for A1/2SA1/2AN and 2.41 A +/- 0.38 kg/day for Saanen) than the rainy season (2.17 A +/- 0.27 kg/day for A1/2SA1/2AN and 2.28 A +/- 0.53 kg/day for Saanen). The MP correlations were very significant (p < 0.05), however low and negative, where it was higher when correlated with RR in Saanen goats. Under the conditions of the present study, it is concluded that the goats were influenced by climatic factors, where the rainy period was more likely to cause thermal stress in the animals.
Keywords: Adaptability; Tropical climate; Heat stress; Dairy goat